Exploring the pathogenesis and clinical implications of asthma, chronic obstructive pulmonary disease (COPD), and asthma-COPD overlap (ACO): a narrative review - Simmalee, Kantapat; Kawamatawong, Theerasuk; Vitte, Joana; Demoly, Pascal; Lumjiaktase, Putthapoom (Frontiers in Medicine, 2025)
The complexity and diversity of the immune response in patients with asthma, chronic obstructive pulmonary disease (COPD), and asthma-COPD overlap present significant challenges for disease management. Relying on a limited number of biomarkers and clinical data is insufficient to fully reveal the immunopathogenesis of these diseases. However, in vitro technologies such as cell analysis, cytokine investigation, and nucleic acid sequencing have provided new insights into the underlying mechanisms of these diseases, leading to the discovery of several biomarkers—including cell degranulation, cell function, secreted cytokines, and single nucleotide polymorphisms—that have potential clinical implications. This paper reviews the immunopathogenesis in asthma, chronic obstructive pulmonary disease, and asthma-COPD overlap and examines the applications of recent in vitro models to detect candidate biomarkers that could enhance diagnostic precision, predict severity, monitor treatments, and develop new treatment strategies. A deeper understanding of the immune response in these diseases, along with the integration of in vitro models into clinical practice, could greatly improve the management of these respiratory diseases, making approaches more personalized and efficient.